Rheological properties of wood/bacterial cellulose and chitin nano‐hydrogels as a function of concentration and their nano‐films properties - Hesamoddin Jannatamani; Ali Motamedzadegan; Mohammad Farsi; Hossein Yousefi (IET Nanobiotechnology)
Abstract In this study, rheological properties of the Wood Cellulose NanoFibers (WCNF), Bacterial Cellulose NanoFibers (BCNF), and Chitin NanoFibers (ChNF) as well as physical properties of films prepared from each nano‐hydrogel were investigated. Each nano‐hydrogel was prepared in 2 concentrations of 0.5 and 1 wt% for rheological study. Rheological properties were measured using a rotational rheometer. The flow behaviour data were fitted with rheological models. Apparent viscosity was higher in higher concentrations of nano‐hydrogels. Herschel‐Bulkley model was the best model for flow behaviour data fitting. BCNF nano‐hydrogels had the highest hysteresis loop while WCNF nano‐hydrogels had the best structure recovery and lowest hysteresis loop. At LVE (Linear Viscoelastic Region), G′ (storage modulus) and G″ (loss modulus) had a constant value, but as strain increased their values decreased. Storage modulus was found to be greater than loss modulus in all samples during frequency sweep test. BCNF nano‐hydrogel showed the lowest frequency dependency. Chitin nanofilms had the highest elongation and stress value.